Revision of Neotropical genera Microraphes Franz, Heteroscydmus Franz and Mimoscydmus Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
Neotropical ant-like stone beetle genera Microraphes Franz, Heteroscydmus Franz and Mimoscydmus Franz are revised. Microraphes pygmaeus Franz, Heteroscydmus yapacariensis Franz and Mimoscydmus brasiliensis Franz are redescribed; Mimoscydmus baruerii Franz is transferred to a new genus Amimoscydmus gen. nov., resulting in Amimoscydmus baruerii (Franz) comb. nov. Together with the large genus Microscydmus Saulcy & Croissandeau all these taxa comprise the smallest known Cyrtoscydmini, with the body length typically below 1 mm, and often as small as nearly half a millimeter. All treated genera are redefined, and morphological structures of all species are illustrated. Unusual transformations of the ventral prothoracic structures found in this group of Scydmaeninae are discussed as putative effects of miniaturization.